ESA measurements using the hybrid fibre-optic reflection measurement system - Morrow, Ivor L.; Clow, N. (Cranfield University, 2009)
Since the introduction of the Wheeler Cap method to measure the radiation efficiency of an Electrically Small Antenna (ESA), there have been several techniques presented in literature that have either enhanced on the method or provided an alternative technique. This paper presents measurements of the radiation efficiency of an electrically small monopole using the Hybrid Fibre-Optic RF Reflection Measurement System (HRS) integrated into the Wheeler Cap. The HRS isolates the ESA from the measurement system [1]. The ESA’s reflection coefficient can then be measured with the isolated ESA inside the Wheeler Cap and in freespace to determine its efficiency. The HRS is also integrated into a far-field measurement range to measure the far-field radiation pattern of the ESA.
To be presented at Loughborough Antennas & Propagation Conference, Loughborough, 16th - 17th November 2009